2002
DOI: 10.1088/0953-8984/14/44/424
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transition in GaN nanocrystals

Abstract: High-pressure in situ energy-dispersive x-ray diffraction experiments on GaN nanocrystals with 50 nm diameter have been carried out using a synchrotron xray source and a diamond-anvil cell up to about 79 GPa at room temperature. A pressure-induced first-order structural phase transition from the wurtzite-type structure to the rock-salt-type structure starts at about 48.8 GPa. The rock-salttype phase persists to the highest pressure in our experimental range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…In contrast, an abundance of almost 100% was reported for the rocksalt phase of bulk GaN at a pressure of less than 60 GPa in most of the previous studies. 4,7,8,12 Our observation was consistent with that for nanocrystalline GaN where the wurtzite to rocksalt phase transition was found to be incomplete even at 63.5 GPa. 9 Similar results were also obtained in other one-dimensional nanomaterials, such as boron nitride nanotubes.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, an abundance of almost 100% was reported for the rocksalt phase of bulk GaN at a pressure of less than 60 GPa in most of the previous studies. 4,7,8,12 Our observation was consistent with that for nanocrystalline GaN where the wurtzite to rocksalt phase transition was found to be incomplete even at 63.5 GPa. 9 Similar results were also obtained in other one-dimensional nanomaterials, such as boron nitride nanotubes.…”
supporting
confidence: 90%
“…1͑b͔͒. All of the previous studies found that the B4-B1 phase transformation was reversible for both bulk GaN and nanocrystalline GaN 4,8,12 indicating that the wurtzite phase was thermodynamically stable in the low pressure region. However, the strongly contrasting, unprecedented decompression behavior of the GaN nanowires characterized by a large hysteresis, suggests that the rocksalt phase is a metastable phase.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…It was also observed that the rock-salt-based structure is more stable at high pressures. For example, even binary nitrides, including GaN and AlN, take on the rock-salt-type structure under high-pressure conditions. However, for the ZnSnN 2 crystal, only the wurtzite phase ( P 6 3 mc ) was obtained at pressures below 7.7 GPa. Additionally, it can be considered that the stronger the ionic bonding, the more likely it is for the crystal to change from a tetra- to a hexacoordinate structure, and the order–disorder transition is determined on the basis of the difference between the ionic radii of the group II and IV cations.…”
Section: Resultsmentioning
confidence: 99%
“…Wen et al [111] have studied the pressure induced phase transition in CdSe and ZnO NCs and found that the transition pressure increases as the nanocrystals size reduces. A pressure induced first-order structural phase transition from wurtzite to rocksalt type structure has been observed in GaN NCs at around 48.8 GPa using x-ray diffraction technique [112]. Theoretically [58] the structural stability and high pressure behavior of AlAs NCs has been analysed in various phases such as wurtzite (B4), zincblende (B3), CsCl (B2) and NaCl (B1), and observes the structural transformations from B3→B1 at around 8.9 GPa, B3→B2 at 7.12 GPa and from B3→B4 at 3.88 GPa, which is probably being the first report.…”
Section: Structural Phase Transitionmentioning
confidence: 98%